Οι επιπτώσεις της οικονομικής κρίσης στην ποιότητα των παρεχομένων υπηρεσιών από την Ανώτατη Εκπαίδευση - Κυριάκου, Αγάθη (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The whole study and implementation is done in Cyprus. The aim of this research project is to investigate the impact of the economic crisis on the quality of services offered by Cyprus Higher Educational Institutions. A survey conducted back in 2012 will be compared to this one to see if the economic crisis indeed has positively or negatively affected the quality of Education System and in what degree. Four (4) Universities in Cyprus were sampled which are Cyprus University of Technology, the University of Cyprus, the European University and the University of Nicosia. The survey also analyzes the international financial crisis that exists worldwide but also how was created out in Cyprus. The requirements of students who have access to the services of their university have also been investigated. The degree of significance/importance and satisfaction of the students was analyzed for all the issues developed in the study’s questionnaire. The study was completed with the creation of the tables and charts conducted by the questionnaires and with conclusions and suggestions for improvement of this situation in Cyprus. A questionnaire was created through a bibliographic review. The sample was collected and then with the help of the Excel program the students' answers were recorded, static analysis was made and tables and graphs were created. Then comments were made about it. This study identified marks for improvement and suggestions of ways to achieve them. The researcher gave his conclusions and suggestions from the analysis in order to properly address the crisis affecting the Education System in Cyprus. According to the researcher the study that was done was successful since the aim and objectives of the research were achieved. Cyprus, and Cyprus education in particular, has proved to face difficulties in many aspects of quality due to the economic crisis. The main results and benefits are the following: Cyprus is facing many difficulties due to financial crisis in comparison with many years ago. The economic crisis has negatively affected both socially and psychologically the customers (students, teachers, administrations).Cyprus Higher Education Institutions can take this project as an example of improvement and focus on the most important problems for improvement. The results of the study show that the difference in significance and satisfaction is quite large for both years. Regarding both, Cyprus University of Technology and the University of Cyprus from the average satisfaction level that existed in questions about quality, there is an increase of 0.548 and 0.714 respectively from the year 2012. However, there is a relatively small decrease in European University and University of Nicosia, 0.338 and 0.712 from the year 2012. As far as the researcher is concerned, she can now work autonomously and deal with α future research of larger and coarse sample.
Keywords: Economic crisis; Higher Education of Cyprus; Degree of materiality; Degree of satisfaction; Οικονομική κρίση; Ανώτατη Εκπαίδευση της Κύπρου; Βαθμός σημαντικότητας; Βαθμός ικανοποίησης